2020
DOI: 10.1097/jfn.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Verbal, Physical, and Sexual Violence Against Healthcare Workers in Ankara, Turkey

Abstract: Background Healthcare professionals work in high-stress, fast-paced settings where individuals from different professions work together and who are exposed to many types of violence. The phenomenon of violence has become a concern of utmost importance for healthcare professionals that should be addressed with due attention. Objectives The aim of this study was to evaluate the verbal, physical, and sexual workplace violence experienced by healthcare prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
2
11
0
3
Order By: Relevance
“…Physicians and men were more likely to be exposed to physical violence (Kitaneh and Hamdan 2012;Abed et al 2016;Wang et al 2018). Nurses and women were more likely to be exposed to sexual harassments (Demirci and Uğurluoğlu 2020). Though one study said physicians were less likely to be exposed to physical attack than nurses (Zafar et al 2013).…”
Section: Vulnerable Groupsmentioning
confidence: 99%
See 3 more Smart Citations
“…Physicians and men were more likely to be exposed to physical violence (Kitaneh and Hamdan 2012;Abed et al 2016;Wang et al 2018). Nurses and women were more likely to be exposed to sexual harassments (Demirci and Uğurluoğlu 2020). Though one study said physicians were less likely to be exposed to physical attack than nurses (Zafar et al 2013).…”
Section: Vulnerable Groupsmentioning
confidence: 99%
“…Studies showed that direct care providers were at significant risk (Pompeii et al 2015). The majority of the studies showed that nurses and women were more likely to be exposed to violence than physicians and men (Algwaiz and Alghanim 2012;Park et al 2015;Abed et al 2016;Ferri et al 2016;Alsaleem et al 2018;Honarvar et al 2019;Demirci and Uğurluoğlu 2020). However, another study observed no significant difference between physicians and nurses regarding the episodes of violence (Kitaneh and Hamdan 2012).…”
Section: Vulnerable Groupsmentioning
confidence: 99%
See 2 more Smart Citations
“…Turkey is well below the average of the OECD countries (8.8) in terms of the number of nurses (2.1) per 1,000 people, and is, in fact, the lowest ranking country among the OECD countries (OECD, 2019). According to a recent study in Turkey, compared with doctors and other medical personnel, nurses were more exposed to sexual, verbal and physical violence (Demirci & Uğurluoğlu, 2020). Factors such as staff insufficiency, excessive workload and workplace violence can cause higher work stress among nurses in Turkey.…”
Section: Introductionmentioning
confidence: 99%